STRATEGI KEPEMIMPINAN TRANSFORMASIONAL KIAI DALAM MENINGKATKAN KINERJA PENGURUS PESANTREN - Miftahur Rizqi (Educational Research Center, 2025)
This study analyzes the transformational leadership style of Kiai and the strategies they apply to improve the performance of administrators at Al Furqan Islamic Boarding School and Miftahul Hasan Al Utsmani Islamic Boarding School. The findings show that Kiai's leadership in the two pesantren effectively integrates the four pillars of transformational leadership, namely ideal influence, inspirational motivation, intellectual stimulation, and individual consideration. This leadership style is reinforced by a series of concrete managerial strategies, including empowering managers through wise delegation of tasks, deliberation and training-based competency development, integrating traditional values with modern innovations, and creating a harmonious work environment and effective supervision and recognition systems. Through this comprehensive approach, Kiai succeeded in transforming administrators into active participants and innovators, which ultimately contributed to the progress of the pesantren and the achievement of noble educational goals. This study uses a qualitative case study method with a multi-case approach, where data is collected through observation, interviews, and documentation, and its validity is guaranteed through triangulation.